PENDAMPINGAN TAHSIN METODE QIRO’ATIL DI RUMAH QUR’AN MANIMPAHOI - Suriyati, Suriyati; Suriati, Suriati; Anis, Muh.; Riska, Riska; Muzaina, Nur; Wahyuni, Sri (LP2M Universitas Islam Ahmad Dahlan, 2025)
This mentoring aims to improve the ability to read the Qur'an well. The target of this activity is 12 female students. The mentoring method is carried out using the qiro'ah and talaqqi methods. Providing solutions to problems that occur by implementing the Qiro'ati learning method. The results of the Qiro'atil method tahsin mentoring program at the Manimpahoi Qur'an House run effectively and have a real positive impact on improving the quality of the students' reading of the Qur'an. This activity not only strengthens the technical ability to read, but also forms a character of love for the Qur'an from an early age. The tahsin mentoring program using the Qiro'atil method at the Manimpahoi Qur'an House has had a significant impact on improving the students' ability to read the Qur'an. Through a systematic and continuous approach, the participants showed progress in the aspects of letter pronunciation, tajwid, and reading fluency. The Qiro'atil method applied has proven effective in forming the habit of reading the Qur'an correctly according to the rules, especially for beginner students or those who still have shortcomings in reading. In addition, this mentoring also strengthens the students' enthusiasm for learning through a humanistic, personal and motivational approach from the mentors